2021
DOI: 10.3390/ma14226874
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Materials Based on Fly Ash, Metakaolin, and Cement for 3D Printing

Abstract: Nowadays, one very dynamic development of 3D printing technology is required in the construction industry. However, the full implementation of this technology requires the optimization of the entire process, starting from the design of printing ideas, and ending with the development and implementation of new materials. The article presents, for the first time, the development of hybrid materials based on a geopolymer or ordinary Portland cement matrix that can be used for various 3D concrete-printing methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 113 publications
(165 reference statements)
0
16
0
Order By: Relevance
“…A single filament in the aramid roving had a diameter of 10 µm. The characteristics of the raw materials used for the research were presented in our previous work [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A single filament in the aramid roving had a diameter of 10 µm. The characteristics of the raw materials used for the research were presented in our previous work [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Further, fly ash and slag, due to their properties being similar to cement, are also suitable alternatives to its partial replacement [ 22 , 23 ]. Fine fly ash has pozzolanic activity [ 24 ] and can improve the compressive strength of the final product [ 25 , 26 , 27 , 28 , 29 ]. Muthusamy et al [ 27 ] showed that concrete, in which 30% of the cement was replaced with fly ash, can be used in the construction industry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geopolymers are concrete-like materials, they can be cast into molds taking the shape of a vessel, they can be a binder or they can be printed with the use of additive technologies [4][5][6][7]. Geopolymers are called alkaline activated materials (due to the first phase of geopolymer formation), they are created by combining aluminosilicate materials with alkaline compounds, strongly basic sodium, potassium or acid phosphates [1,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…For more than a decade, the researches and applications of polymers as 3D-printed building mortar materials have attracted more and more attention from scientists. As green building materials, geopolymers can replace cement-based materials as 3D-printed building mortars in the future [ 27 , 28 , 29 ]. In this paper, the properties of the polymer fiber-reinforced 3D-printed building mortars used in recent years are summarized.…”
Section: Introductionmentioning
confidence: 99%